Offtake as a means of implementing economic diplomacy in modern society - Nygmetova Б.М.; Baissultanova К.Ч. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
In the modern world, economic diplomacy is becoming an increasingly important tool in the foreign policy of states. One of the methods of its implementation is offtake, that is, an agreement to purchase a certain volume of goods or services under pre-agreed conditions. This is a tool of economic diplomacy that can be successfully implemented in modern society to achieve development goals and strengthen economic relations. One of the main advantages of an off-take is the reduction of risks for both parties. This allows the manufacturer to find out the exact demand for their products and ensure stable production volumes, and the consumer – long-term supplies at a low price. This also helps to establish trust between the parties, which is of great importance for expanding economic ties. Offtake is also an effective tool for attracting investment. By guaranteeing the purchase of a product or service, companies can attract financial resources to expand production and improve the quality of their products. This, in turn, contributes to economic growth and development of the country as a whole. In modern society, off-take stands out as one of the effective means of developing economic diplomacy. This is especially true for developing countries that are seeking to diversify their economies and attract foreign investment. Offtake can be a powerful incentive for investors because it provides stability and predictability in the need for a product or service. This article explores the role of off-take in the context of economic diplomacy, as well as its impact on international relations and economic cooperation. The article examines examples of off-take agreements in various sectors such as energy, agriculture, trade and investment, and also analyzes their contribution to the development of economic relations between countries and corporations.